Peningkatan Keterampilan Menulis Se Presenter melalui Strategi Cooperative Integrated Reading and Composition (CIRC) - Sri Moerni (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The writing skills of the presenters of class X IPS 1 SMA Negeri 10 Yogyakarta for the 2022-2023 academic year are still low. Students do not have sufficient vocabulary, and knowledge related to grammar is still low. The purpose of this study was to improve the presenter's writing skills with the Cooperative Integrated Reading and Composition strategy. The method used is Classroom Action Research referring to the Kemmis & Taggart model, which begins with planning, implementing, observing and reflecting. This research was conducted in two cycles, each beginning with planning, implementation, observation and reflection. Each cycle consists of two meetings. The results showed that: 1) the steps applied to this strategy included understanding the concept, exploration and application and ending with publication 2) the percentage of learning completeness in cycle one was 69.5% with an average value of 75, while the learning completeness cycle second by 84% with an average of 77.64. The increase in the percentage of learning outcomes in cycle one and cycle two was 17.26%. Thus it can be concluded that by combining reading and writing competencies and group work in the Cooperative Integrated Reading and Composition strategy, students' writing skills can be improved.